Pengaruh Media Wordwall Pada Pembelajaran Bahasa Indonesia Terhadap Hasil Belajar Kognitif Siswa: The Impact of Wordwall Media on Indonesian Language Learning On Students' Cognitive Learning Outcomes - Sari, Yani Muriyan; Rosa, Yanis (Literasi: Jurnal Pendidikan Guru Indonesia, 2025)
Good learning can be seen from the atmosphere of the class and the interaction between the teacher and students. The use of conventional and unvaried learning media causes students to be unenthusiastic and will affect student learning outcomes. Interesting media will influence learning activities, when students judge that what the teacher shows is interesting then they will be encouraged to know what the teacher is saying so that the learning process will be more enjoyable. Based on these problems, the problem formulation was obtained: 1) Can the Wordwall learning media increase student activity in learning Indonesian, material on intrinsic story elements for class V MIN 8 South Aceh?. 2) What is the influence of the Wordwall learning media on the learning outcomes of class V MIN 8 South Aceh students in learning Indonesian regarding the intrinsic elements of stories? Research conducted at MIN 8 South Aceh aims to determine the influence on the activities and learning outcomes of class V students on the application of Wordwall learning media. This research design is truly experimental in the form of a posttest only control design. The data collection technique in this research is by tests, namely posttests and student activity sheets. Hypothesis testing analysis techniques use the t-test, and student activity sheets use percentages. The results of the research show that there is an influence of the Wordwall learning media on students' learning outcomes. From the results of the analysis it is obtained that tcount = 3.385 > ttable = 2.028, so Ha is accepted, which means there is an influence on learning outcomes with the application of the Wordwall learning media. Student activity also increased with percentage results from 2556% to 3513%. This means that there is a significant difference in posttest scores between the experimental class and the control class. It can be concluded that there is an influence of the Wordwall learning media on student learning outcomes regarding the intrinsic elements of stories.